IoT business guarantee method based on behavioral portrait - Longgang ZHAO; Hansheng LIU; Feng WANG; Shuang DI (Dianxin kexue)
IoT terminals have the characteristics of large user base, many manufacturers and numerous scenarios.It is difficult to unify the standard of poor quality and to locate the segment in the routine maintenance process.Aiming at the above phenomenon, a business guarantee method based on behavior portrait was proposed.Firstly, based on the distribution characteristics of key indicators, a fingerprint model of enterprise quality deficit was constructed, and the idea of mean shift clustering in statistical learning was used to realize the accurate construction of quality deficit index system.Then, to solve the problem that it was difficult to distinguish between the measurement terminal and the poor quality terminal, and it was difficult to identify the weak coverage terminal, a single user poor quality behavior portrait was constructed to effectively ensure the accuracy of the model.Finally, the pilot and analysis were carried out in the current network environment to provide reference for the IoT business guarantee.